Brands and Branding: strategy to build and nurture brands - Aggarwal, Ashita; Commuri, Suraj (London Routledge, 2024)
This volume examines the importance of strategic brand imaging and brand management. It covers the fundamentals of launching, growing, leveraging, and managing brands in a global context, the strategic decisions related to brand building, and the integration of the 4Ps in implementing the brand strategy. The book presents a practical perspective on building brands through social media and using artificial intelligence technologies. Readers will get a clear introductory understanding about the role of consumer behavior, the research methods that every brand manager must be familiar with, brand architecture, portfolio, brand equity, and valuation.
Keywords: Asian Studies; Business, Management and Marketing; Marketing Communications